No Difference between Spinal Anesthesia with Hyperbaric Ropivacaine and Intravenous Dexmedetomidine Sedation with and without Intrathecal Fentanyl: A Randomized Noninferiority Trial - Seung Cheol Lee; Tae Hyung Kim; So Ron Choi; Sang Yoong Park (Pain Research and Management)
To enhance the duration of single-shot spinal anesthesia, intrathecal fentanyl and intravenous dexmedetomidine are widely used as adjuvants to local anesthetics. This noninferiority trial evaluated whether hyperbaric ropivacaine alone can produce a noninferior duration of sensory block in comparison to hyperbaric ropivacaine with intrathecal fentanyl in patients under dexmedetomidine sedation. Methods. Fifty patients scheduled for elective lower limb surgery under spinal anesthesia were randomly assigned in a double-blind fashion to receive either hyperbaric ropivacaine 15 mg (Group R) or hyperbaric ropivacaine 15 mg with intrathecal fentanyl 20 μg (Group RF). Intravenous dexmedetomidine (1 μg/kg for 10 min, followed by 0.5 μg/kg/h) was administered in both groups. The primary outcome of this study was the time to two-dermatomal regression of sensory block. The noninferiority margin for the mean difference was −10 min. Characteristics of the block, intraoperative and postoperative side effects, postoperative pain score, and analgesic consumption were assessed as secondary outcomes. Results. There was no difference in the two-dermatomal regressions of sensory block between the two groups (Group R 70.4 ± 10.2 min, Group RF 71.2 ± 12.4 min, p = 0.804) with a mean difference of 0.8 min (−7.2 to 5.6, 95% confidence interval). Thus, the noninferiority of hyperbaric ropivacaine alone was established. There were no significant differences in the secondary outcomes between the two groups. Conclusions. Under intravenous dexmedetomidine sedation, the duration of spinal anesthesia with hyperbaric ropivacaine alone was noninferior to that of hyperbaric ropivacaine with intrathecal fentanyl. This suggests that addition of intrathecal fentanyl to hyperbaric ropivacaine may not be necessary in patients receiving intravenous dexmedetomidine.